AL-QURAN DALAM PENGEMBANGAN PENDIDIKAN ISLAM DAN TEKNOLOGI DI ERA 4.0 - Cut Nadia Syahfira; Dedi Masri Email; Muhammad Alfiansyah; Iskandar Dzulkarnain Nasution (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
This study describes various problems of the Qur'an in the development of Islamic education and technology in the 4.0 era as well as some answers to overcome existing problems. The type of research in this paper is descriptive qualitative. The data collection technique used was the Library Research method with various reading sources such as pre-existing books or journals. The results of this study indicate that the Al-Qur'an in the development of Islamic education and technology in the 4.0 era consists of: (1) steps to overcome technological backwardness in the world of Islamic education which are always related to the Al-Qur'an, (2 ) Steps that need to be considered by an educator to understand digital skills in the learning process, (3) Some preparations that must be prepared before becoming an educator (teacher) so that learning goes well, (4) Methods that need to be studied and prepared by educators (teachers) before providing teaching materials in the classroom.